2010
DOI: 10.1193/1.3479947
|View full text |Cite
|
Sign up to set email alerts
|

Reconnaissance Observation on Bridge Damage Caused by the 2008 Wenchuan (China) Earthquake

Abstract: Following the 2008 Wenchuan (China) earthquake, the civil engineers association from Taiwan immediately dispatched a team to the affected region to collect information about the structural and geotechnical damage, and to provide information for seismic assessment, retrofitting and reconstruction planning. This team reached the damaged areas close to the epicenter—including Chengdu, Dujiangyan, Pongzhou, Xiaoyudong, Mianzhu, Zhiulong, Wudu, Hanwang, Hsuanko, Yingxiu (epicenter), and Highway 213—to survey the af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The Ms 8.0 Wenchuan earthquake caused frequent secondary disasters, including debris flows, landslides, collapses, and floods, as well as subsequent deterioration in the ecological environment of the Longxi River Basin [31]. The changes caused by secondary disasters in the geomorphology and river system induced a large area of vegetation destruction and reshaped land use patterns [32]. Our previous study showed that unutilized land induced by secondary disasters replaced grassland as the second dominant land type, accounting for 15.99% of the Longxi River Basin's area in 2009 [8].…”
Section: Introductionmentioning
confidence: 99%
“…The Ms 8.0 Wenchuan earthquake caused frequent secondary disasters, including debris flows, landslides, collapses, and floods, as well as subsequent deterioration in the ecological environment of the Longxi River Basin [31]. The changes caused by secondary disasters in the geomorphology and river system induced a large area of vegetation destruction and reshaped land use patterns [32]. Our previous study showed that unutilized land induced by secondary disasters replaced grassland as the second dominant land type, accounting for 15.99% of the Longxi River Basin's area in 2009 [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Anagnostopoulos [9] has identified pounding damage in his work during the Northridge (1994) and Kobe (1995) quakes. Pounding criteria between adjacent building structures and resulting damage were also examined by other researchers, e.g., the Chi-Chi earthquake in 1999 [10] and the Wenchuan earthquake in 2008 [11].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of pounding damage between adjacent structures were conducted based on past and present earthquakes. Pounding damage was acknowledged in numerous extreme earthquakes, such as the 1999 Taiwan Chi-Chi earthquake [8], and the 2008 Wenchuan earthquake [9]. After the 2011 Christchurch earthquake, pounding incidents between neighbouring buildings as well as bridge structures were observed and reported [10,11].…”
Section: Introductionmentioning
confidence: 99%